Representation of Gretel's Crisis of Trust in the Secret Magic Control Agency's Fairy Tale Adaptation - Prameswari, Pradypta; Alamsyah, Dicky Samudra; Sanjaya, Rizal Bagus (Nexus Publishing NXP, 2025)
This research analyses the representation of Gretel's crisis of trust in the film Secret Magic Control Agency using Roland Barthes' theory. The main focus of this research is to identify how the crisis of trust is reflected in Gretel's behaviour and character interactions. This research reveals the factors that influence the crisis of trust, including environmental influences and relationship dynamics with other characters, as well as experiences inspired by the classic story of Hansel und Gretel from the Brothers Grimm. In addition, this research also discusses the role of film as a learning medium. Referring to Weisarkurnai's (2017) opinion, films are considered aesthetic works and information tools that are entertaining and educational. On the other hand, the moral, ethical, and ethical values contained in fairy tales function as a means of learning for children, as explained by Setiawan (2018). Through this analysis, it is expected to understand the complexity of Gretel's character and the relevance of the values contained in the narrative.